ESSENTIALITIES CONCERNING THE COMPETITION POLICY IN THE EUROPEAN UNION, THE 2012-2016 PERIOD - Florentina Cristina BALDAN (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The paper “Essentialities concerning the competition policy in the European Union, the 2012-2016 period” presents the decisions adopted at European Union level in relation to the breech of the competition rules by the Member States. In the first part of the paper, I drew a parallel between the state aids granted at EU level for the banking system, deeply affected by the economic crisis, and the aids granted for supporting other sectors. Afterwards, I made a brief presentation of the main anti-competitive and of the decisions related to them in the analysed period.